2020
DOI: 10.1002/ece3.6736
|View full text |Cite
|
Sign up to set email alerts
|

Defining relictual biodiversity: Conservation units in speckled dace (Leuciscidae: Rhinichthys osculus) of the Greater Death Valley ecosystem

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 121 publications
(128 reference statements)
9
29
0
Order By: Relevance
“…As with prior studies (Derkarabetian et al 2019; Mussmann et al 2020), we also found considerable variation among methods, some of which can be attributed either to idiosyncrasies in the data or to algorithms and their implementation. For example, among RF methods iso MDS generally yielded smaller K (Figure 3d), attributed by Derkarabetian et al (2019) to the retention of only two dimensions.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…As with prior studies (Derkarabetian et al 2019; Mussmann et al 2020), we also found considerable variation among methods, some of which can be attributed either to idiosyncrasies in the data or to algorithms and their implementation. For example, among RF methods iso MDS generally yielded smaller K (Figure 3d), attributed by Derkarabetian et al (2019) to the retention of only two dimensions.…”
Section: Discussionsupporting
confidence: 80%
“…In contrast to Derkarabetian et al (2019), we found t -SNE the most inclined to produce inconsistent groupings, a pattern most prevalent with the gap statistic (Supplementary Information B1-B60). Mussmann et al (2020) concurred, although in their case it was PAM+HMSW. We see this as an inherent problem relating to data structure.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Speciation in the Karnali River Basin could thus be poorly resolved with respect to mitochondrial divergence, with a genetic signal likely obscured by the limited framework within which ancestral alleles could sort, allowing novel haplotypes to arise. More refined molecular approaches, such as reduced-representation genomics [32,33,34,49,50], could potentially provide the necessary resolution, although it will again be compounded by the rampant polyploidy found in Cyprininae.…”
Section: Macrophthalmus S Nepalensis S Raraensis) Occupy Separatementioning
confidence: 99%